Adhesive thermosensitive gels for local delivery of viral vectors. Issue 9 (20th May 2019) - Caronia, Jeanette M.; Sorensen, Daniel W.; Leslie, Hope M.; van Berlo, Jop H.; Azarin, Samira M.
Abstract: Local delivery of viral vectors can enhance the efficacy of therapies by selectively affecting necessary tissues and reducing the required vector dose. Pluronic F127 is a thermosensitive polymer that undergoes a solution–gelation (sol–gel) transition as temperature increases and can deliver vectors without damaging them. While pluronics can be spread over large areas, such as the surface of an organ, before gelation, they lack sufficient adhesivity to remain attached to some tissues, such as the surface of the heart or mucosal surfaces. Here, we utilized blends of pluronic F127 and polycarbophil (PCB), a mucoadhesive agent, to provide the necessary adhesivity for local delivery of viral vectors to the cardiac muscle. The effects of PCB concentration on adhesive properties, sol–gel temperature transition and cytocompatibility were evaluated. Rheological studies showed that PCB decreased the sol–gel transition temperature at concentrations >1% and increased the adhesive properties of the gel. Furthermore, these gels were able to deliver viral vectors and transduce cells in vitro and in vivo in a neonatal mouse apical resection model. These gels could be a useful platform for delivering viral vectors over the surface of organs where increased adhesivity is required. Abstract : Pluronic F‐127 is useful for delivering viral vectors but lacks sufficient adhesivity to remain attached to tissue surfaces in vivo. In this work, Pluronic F‐127 was combined with the adhesive agent polycarbophil, resulting in gels with tunable adhesivity and sol‐gel transition temperature. When blended with an adenovirus, the gels were able to achieve in vitro and localized in vivo transduction, with no positive expression observed in organs not in contact with the gel in vivo.